Management of established coronary artery disease in aircrew with previous myocardial infarction or revascularisation. (13th November 2018) - Davenport, Eddie D; Syburra, Thomas; Gray, Gary; Rienks, Rienk; Bron, Dennis; Manen, Olivier; d'Arcy, Joanna; Guettler, Norbert J; Nicol, Edward D
Abstract : This manuscript focuses on the broad aviation medicine considerations that are required to optimally manage aircrew with established coronary artery disease (CAD) without myocardial infarction (MI) or revascularisation (both pilots and non-pilot aviation professionals). It presents expert consensus opinion and associated recommendations and is part of a series of expert consensus documents covering all aspects of aviation cardiology. Aircrew may present with MI (both ST elevation MI (STEMI) and non-ST elevation MI (NSTEMI)) as the initial presenting symptom of obstructive CAD requiring revascularisation. Management of these individuals should be conducted according to published guidelines, ideally with consultation between the cardiologist, surgeon and aviation medical examiner. Return to restricted flight duties is possible in the majority of aircrew; however, they must have normal cardiac function, acceptable residual disease burden and no residual ischaemia. They must also be treated with aggressive cardiac risk factor modification. Aircrew should be restricted to dual pilot operations in non-high-performance aircraft, with return to flying no sooner than 6 months after the event. At minimum, annual follow-up with routine non-invasive cardiac evaluation is recommended.